JUSTICE IN THE VIEWS OF GEN Z IN SINGARAJA CITY: AN ANALYSIS OF THE INFLUENCE OF SOCIAL MEDIA ON GEN Z OPINION FORMATION ON JUSTICE IN SOCIETY - Yudana, I Made; Sukadi, Sukadi; Putri, Nia Kharisma; Ramadhani, Muhammad Raditya; Wirayuda, I Komang Aldi; Andani, Ketut Tya; Aprilianti, Devi; Lestari, Deah Tri (Ganesha Civic Education Journal, 2025)
This study aims to analyze perceptions of justice among Generation Z (Gen Z) in Singaraja City and explore how social media influences their opinion formation regarding the principles of justice in society. In the digital era marked by the rapid development of information technology, social media has become a crucial digital public space for disseminating information, shaping views, and influencing the thinking of the younger generation. Gen Z, growing up and developing alongside technological advancements, has made social media an integral part of their daily lives. This study uses a descriptive qualitative approach, using observational techniques to observe Gen Z's online activities on platforms such as Instagram, TikTok, and Twitter. The results indicate that social media provides extensive access to information and discourse on justice, which in turn can increase their social awareness, empathy, and engagement in social justice issues